Instructional Materials on Legend Texts Based on Local Wisdom for Junior High School Students - Laraswati, Nadya; Nuryanti, Mira; Susilo, Jimat (Universitas Swadaya Gunung Jati, 2024)
One of the strategic efforts to internalize local wisdom values is through the design, development, and implementation of instructional materials rooted in local cultural heritage. However, in practice—particularly in the city of Cirebon—existing teaching materials have yet to adequately reflect the richness of local identity and traditions. This study aims to (1) describe the design of supplementary teaching materials informed by a needs analysis of students, and (2) examine the outcomes of implementing legend-based instructional materials for seventh-grade students at the junior secondary school level (SMP/MTs). Employing a descriptive-analytical research method, this study seeks to analyze both the development process and the effectiveness of the localized legend text materials. The findings indicate that the developed teaching materials are highly valid and suitable for classroom use, although minor revisions are required to enhance the overall quality and completeness of the textbook.